Community Perceptions on Cultural Preservation and Local Economic Benefits In The Ngarantek Sawa Bahu Festival - Christianto, Jery; Dedy (Politeknik Pariwisata NHI Bandung, 2025)
This research investigates community perceptions regarding the preservation of cultural heritage and the associated local economic benefits resulting from the Ngarantek Sawa Bahu Festival, conducted in Lumar District, with a focus on Tiga Berkat Village. As a traditional Dayak ritual, the festival embodies deep spiritual and social significance and functions as an important mechanism for maintaining cultural identity. Employing a quantitative methodology, the study utilized stratified random sampling to survey 100 respondents, comprising traditional leaders, local residents, MSME stakeholders, event organizers, and visitors. Data were obtained through a Likert-scale questionnaire and analyzed using descriptive statistics. The results reveal a high level of public agreement on the festival’s role in cultural preservation, community identity reinforcement, and intergenerational transmission of values. Furthermore, the festival is perceived to yield meaningful economic outcomes, including increased revenues for local MSMEs, the creation of temporary employment, and heightened local consumption. The study advocates for strategic efforts to strengthen community involvement, encourage culturally informed innovation, ensure active governmental support, enhance MSME capacities, and foster multi-stakeholder collaboration to sustain both cultural and economic contributions.